Endocrine changes in women with a medically indicated abortion: the study design - Romanova Zuzana; Kornanova Eva; Garafova Alexandra; Borovsky Miroslav; Jezova Daniela (Sciendo, 2022)
A strongly psychosocially demanding situation in the life of a woman is the option of medically indicated abortion. Here we present the design of an ongoing study aiming to examine the stressfulness of life events related to medically indicated abortions by measuring cortisol concentrations in the participants' hair and saliva. Pilot results show high salivary cortisol concentrations in the majority of the women one day before induced abortion. In half of the group, two months after the abortion, hair cortisol concentrations were higher in comparison to cumulative values from two months before. There were no changes in the second half.